LB03.07: ANTIHYPERTENSIVE THERAPY AND RISK OF ADMISSIONS FOR MOOD DISORDERS. (June 2015) - Boal, A.; Smith, D.; Muir, S.; Touyz, R.M.; Dominiczak, A.F.; Padmanabhan, S.
Abstract : Objective: To explore if calcium channel blocker (CCB) treatment is associated with a different or lower risk of mood affective disorder hospital admissions compared to other antihypertensive drugs. Design and method: Two cohorts were studied: the Glasgow Blood Pressure Clinic (GBPC) and a hospital cohort of admissions from two Glasgow hospitals from 1980 to March 2013. These cohorts included 17, 610 and 525, 046 patients respectively. Prescription refill data from 2004–2013 was used to create monotherapy groups for ACE inhibitors /angiotensin-receptor blockers (AA), beta blockers (BB) and CCB with duration >90 days and a control of no antihypertensive exposure in the hospital cohort. Only prescriptions started after the 1st of April 2004 were included to exclude prevalent use. In the GBPC and hospital cohort, patients were >18 years of age and 40–80 years respectively. Admissions were classified as ICD-10 F30–39 or ICD-9 295–7. Results: There were 1, 927 eligible patients with 31 incident admissions for mood disorders in the GBPC over 10 years and 144, 087 with 302 admissions over 5 years in the hospital cohort. Mean ages were 58 and 56 respectively. After adjustment for age at prescription and sex in both cohorts and additional baseline demographics of blood pressure, height, weight, BMI, smoking and alcohol consumption, eGFR and cardiovascular disease in the GBPC, BB showed a higher risk of admission (HR: 3.2, [95% CI: 1.2–8.6], P = 0.017) compared to AA in the GBPC. In the hospital cohort compared to controls of no antihypertensive exposure BB (1.6[1.1–2.4], P = 0.009) and CCB (1.8[1.1–3.0], P = 0.014) showed higher risks (Figure 1). Figure. No caption available. Conclusions: Calcium antagonists may exert similar effects on mood symptoms compared to beta blockers. This association has not been previously recognised.